2014
DOI: 10.18052/www.scipress.com/ilshs.34.53
|View full text |Cite
|
Sign up to set email alerts
|

Gender Participation in University Education in Nigeria: Closing the Gap

Abstract: The National Policy on Education stipulated that there is need for equality of educational opportunities to all Nigerian children, irrespective of any real or imagined disabilities, each according to his or her ability. It further stressed that there will be the provision of equal access to educational opportunities for all citizens of the country at the primary, secondary and tertiary levels both inside and outside the formal school system. In spite of this policy commitment there still exists a wide gender d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In terms of equity and access, not only has there been reports of disparity in enrollment statistics based on gender, cases of wide gaps in academic attainment abounds. Mukoro (2014) observed that there seems not to be comparative increase in enrollment rate of females as for the males over the years. This trend was attested to by Oloyede and Lawal (2008) who added that male graduates continued to exceed those of females at both undergraduate and post-graduate levels.…”
Section: Introductionmentioning
confidence: 89%
“…In terms of equity and access, not only has there been reports of disparity in enrollment statistics based on gender, cases of wide gaps in academic attainment abounds. Mukoro (2014) observed that there seems not to be comparative increase in enrollment rate of females as for the males over the years. This trend was attested to by Oloyede and Lawal (2008) who added that male graduates continued to exceed those of females at both undergraduate and post-graduate levels.…”
Section: Introductionmentioning
confidence: 89%
“…For them, this does not only amount to undue advantage being accorded the latter group but also results in the mass recruitment of candidates who are less able to cope with higher education or contribute positively to improved quality of output. They have thus condemned the quota admission system as only serving to exacerbate the problems of access, equity and quality in higher education (Adeyemi, 2001;Agboola and Ofoegbu, 2010;Imabekhai, 2006;Kanyip 2013;Mukoro, 2014) as they lament the poor performance of those admitted and the possible exclusion of the better performing ones.…”
Section: Deconstructing 'Disadvantage' -Rethinking Access Barriers Fomentioning
confidence: 99%
“…The above strand of criticism is strengthened by Nigeria's liberalist philosophy of education and the conditions of the educational system. Thus some subscribers to merit argue that according to Nigeria's educational philosophy which promises a right to equal opportunities for all citizens according to his or her ability (Federal Republic of Nigeria, 2004;Abdulkareeem and Muraina, 2014;Mukoro, 2014), any other arrangements for access besides academic ability compromises uniform quality standards. Especially as Nigeria's education system does not appear to cater for the differing educational needs of its highly diversified range of students, the country's practical redefinition of 'equal opportunities' on the basis of positive discrimination appears untenable.…”
Section: The Notion Of 'Merit' and The (Neo) Liberal Ideals Of Equal mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem did not begin with university enrolment, but far back to primary education. British Council Report [4] reported that, at the primary school level, fewer girls than boys enrolled in school, and the majority of out-of-school children are girls. The difference is even more pronounced in the female participation in STEM courses when compared with that of the male counterparts [2].…”
Section: Introductionmentioning
confidence: 99%